Hyperglycemia in Pregnancy: Recent Diagnostic Criteria and Pharmacologic Treatment for Glycemic Contro - John M.F. Adam; Fabiola M.S. Adam (Indonesian Society of Obstetrics and Gynecology, 2012)
Hyperglycemia in pregnancy, or formerly known as gestational diabetes mellitus, is defined as carbohydrate intolerance of variable severity with onset or first recognition during pregnancy. The classical screening and diagnosis of hyperglycemia in pregnancy is the twosteps screening, consists of 50 gram glucose load and follow by 3- hour 100 gram oral glucose test for those who were screening positive. The diagnosis of hyperglycemia in pregnancy is made if at least two abnormal elevated values i.e. fasting > 95 mg/dl, 1 hour > 180 mg/dl. 2 hour > 155 mg/dl, and 3 hour > 140 mg/dl. The International Association of Diabetes and Pregnancy Study Groups Consensus Panel (IADPSG) in 2010 and the American Diabetes Association in 2011 change the method of screening and diagnostic criteria. In the new method of screening all pregnant woman, not only the high risk group, should be screened using oral glucose tolerance test with 75 gram of glucose. The new diagnosis criteria need only one abnormal plasma glucose value i.e. fasting > 92 mg/dl or 1 hour > 180 mg/dl, or 2 hour > 153 mg/dl. There is debate which criteria should be used universally, since the new criteria will increase the prevalence of hyperglycemia in pregnancy. In most diabetic clinics, especially in the North America, besides medical nutrition therapy, insulin remains the mainstay of treatment for this patient. However, for those women who cannot afford insulin or do not wish to take insulin, glibenclamide and metformin, may be offered as an alternative. Most experts will prefer to use metformin, since it does not increase body weight and also has an insulin sensitivity effect. Keywords: hyperglycemia in pregnancy, IADPSG criteria, pharmacologic treatment